HVAC visualization toolkit - Zhang, Yin (2013)
Nowadays, the idea of automation control and monitoring is applied to all kind of industrial systems, plants and building management. The aim of the automation and monitoring technology is to reduce energy cost, save maintenance cost and collect more information for user to make operation decisions. This project, HVAC Visualization Toolkit, is to develop a generic HVAC visualization component toolkit, based on the principles behind visual analytics, for dynamically exploring time-varying, geographically referenced and multivariate attributes simultaneously. It provides the features to help operator view real time status of building’s HVAC condition on Temperature, Humidity, Air Flow and other relevant properties. Operator is able to remotely monitor and control the HVAC Units, to achieve the main goal of saving energy and cost.